Pengaruh Penerapan Pembelajaran Flipped Classroom Terhadap Kemampuan Komunikasi Matematika Peserta Didik Kelas X SMA - Anwar, Fauziah (RC-INSTITUT, 2019)
The mathematical communication skill is an important aspect and should be achieved in the learning process of mathematics. The importance of mathematical communication skil for students make this capability need to be improved in the learning process of mathematics in every level of education. But, in fact mathematics communication skill of grade X IIS SMA Pembangunan Laboratorium UNP still low. One of the solution of problem is imprementing flipped classroom learning in the mathematics learning process. The purpose of the research is to analyze the students mathematics communication skill that be tought using flipped classroom is better than using conventional learning in the grade X IIS SMA Pembangunan Laboratorium UNP. This research used sample random sampling grade X IIS 4 as experimental class and grade X IIS 3 as control class. Final test data analysis of mathematics communication skill that is used is t test on real stage α=0,05, so get P-value=0,008. Because P-value < α, so accept H0. It can be concluded that students mathematic communication skill by using flipped classroom learning better than conventional learning in grade X IIS SMA Pembangunan Laboratorium UNP.